Preparation method and application of Cl-doped Cu2O / Cu3SnS4 composite photocatalyst
By constructing a Cl-doped Cu2O/Cu3SnS4 composite photocatalyst and optimizing the heterojunction structure and energy band regulation, the problems of low efficiency, poor stability and poor selectivity of Cu2O-based photocatalysts were solved, and the effect of efficient catalytic reduction of CO2 to high-value-added hydrocarbons was achieved.
Patent Information
- Application Number
- CN202510800496.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2025-09-16
AI Technical Summary
Existing Cu2O-based photocatalysts have problems with low efficiency, poor stability and poor product selectivity in the photocatalytic CO2 reduction process, especially it is difficult to efficiently reduce CO2 to high-value-added hydrocarbons.
By constructing a Cl-doped Cu2O/Cu3SnS4 composite photocatalyst, optimizing the heterojunction structure and regulating the band structure of Cu2O, combined with Cl- doping to form a stable structure in the Cu2O lattice, charge separation is promoted and photocorrosion is inhibited, thus achieving a synergistic effect between Cu2O and Cu3SnS4.
The photogenerated carrier separation efficiency is significantly improved, the catalytic activity and stability are enhanced, and the selectivity of efficient catalytic reduction of CO2 to high value-added products such as CO, CH4 and C2H4 is achieved. The cycle stability is improved and the photocatalytic activity is enhanced.
Smart Images

Figure CN120644219A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic CO2 reduction, and in particular to a preparation method and application of a Cl-doped Cu2O / Cu3SnS4 composite photocatalyst. Background Art
[0002] With the overconsumption of fossil fuels and the resulting dramatic increase in atmospheric carbon dioxide (CO2) concentrations, finding sustainable energy solutions and mitigating the greenhouse effect have become global challenges. Photocatalytic CO2 reduction technology, which uses solar energy to convert CO2 into valuable hydrocarbon fuels (such as methane and methanol), is considered a promising "carbon neutrality" strategy. The core of this technology lies in the development of efficient, stable photocatalysts that can fully utilize the solar spectrum.
[0003] Currently, there are many types of semiconductor materials used for photocatalytic CO2 reduction, but the following key bottlenecks are common:
[0004] Low efficiency: The rapid recombination of generated electron-hole pairs severely limits the photoquantum efficiency and catalytic activity.
[0005] Poor stability: Some materials with good visible light response (such as cuprous oxide, Cu2O) are prone to photocorrosion during the photocatalytic process (oxidation by self-generated photogenerated holes), resulting in rapid decay of catalytic activity.
[0006] Poor product selectivity: It is difficult to reduce CO2 to target high-value-added hydrocarbons with high selectivity.
[0007] To overcome the limitations of single materials, constructing heterojunction composites has become an effective strategy. Among them, the p-type semiconductor cuprous oxide (Cu2O) has attracted attention due to its suitable band gap (~2.0 eV, capable of absorbing visible light) and relatively negative conduction band position (favoring CO2 reduction). However, its inherent photocorrosion problem severely restricts its practical application. On the other hand, copper tin sulfide (such as Cu3SnS4) is also a p-type semiconductor with visible light response (band gap of approximately 1.5 eV) and is considered to have relatively good chemical stability. Combining Cu2O with Cu3SnS4 theoretically combines the advantages of both: Cu2O provides strong reducing ability, while Cu3SnS4 provides stability and extends the light absorption range. Simultaneously, the heterojunction interface is expected to promote the effective separation of photogenerated carriers, thereby improving overall catalytic activity and stability.
[0008] However, the performance of existing Cu2O-based heterojunction photocatalysts (including Cu2O / Cu3SnS4) still has much room for improvement:
[0009] The interfacial charge transfer efficiency still needs to be optimized: the construction quality of the heterojunction directly affects the charge separation efficiency.
[0010] The stability problem of Cu2O has not been fundamentally solved: even in a composite system, the photocorrosion tendency of the Cu2O component still exists, affecting long-term stability.
[0011] Number and properties of active sites: The surface properties and active sites of the material are crucial to CO2 adsorption and activation and need to be further regulated.
[0012] Therefore, there is an urgent need to develop a new, efficient and stable photocatalyst, which should have an optimized heterojunction structure to promote charge separation, enhance the stability of the Cu2O component and the overall catalytic activity, thereby significantly improving the efficiency and product selectivity of photocatalytic CO2 reduction. Summary of the Invention
[0013] A problem with the prior art is that conventional Cu2O photocatalysts have poor selectivity for reducing CO2, making it difficult to reduce CO2 to high-value hydrocarbons. To address this technical issue, the present invention provides a Cl-doped Cu2O / Cu3SnS4 composite photocatalyst, the preparation of which includes the following steps:
[0014] (1) cuprous oxide, tin salt and sulfur source are dissolved in deionized water, and Cu3SnS4 is prepared by a hydrothermal method under high temperature, high pressure and closed reaction conditions;
[0015] (2) Add the Cu3SnS4 obtained in step (1) to the copper acetate aqueous solution, stir and disperse evenly, then add the alkaline solution to the reaction system, continue stirring to form a blue flocculent precipitate in the reaction system, and add the hydroxylamine hydrochloride aqueous solution to the reaction system after the reaction is completed. 2+ All reduced to Cu + , and then the solid product is collected by solid-liquid separation. After the surface of the solid product is cleaned and dried, a Cl-doped Cu2O / Cu3SnS4 composite photocatalyst is obtained.
[0016] Preferably, the tin salt is tin tetrachloride hydrate.
[0017] Preferably, the sulfur source is cysteine.
[0018] Preferably, the temperature of the hydrothermal reaction is 140° C. and the reaction time is at least 12 h.
[0019] Preferably, cuprous oxide is prepared by a precipitation method comprising the steps of:
[0020] Surfactant and Cu 2+The source is added to deionized water and stirred to disperse evenly. A precipitant is then added to the reaction system. After stirring to react to generate a blue flocculent precipitate, a reducing agent is added. The stirring reaction is continued until an orange solid precipitate is generated in the reaction system. The obtained precipitate is surface washed and dried to obtain cuprous oxide.
[0021] Preferably, the Cu 2+ The source is copper chloride hydrate.
[0022] Preferably, the surfactant is SDS.
[0023] Preferably, the precipitant is an alkaline solution.
[0024] Preferably, the reducing agent is an aqueous solution of hydroxylamine hydrochloride.
[0025] The present invention has the following beneficial effects:
[0026] The present invention provides a method for preparing a Cl-doped Cu2O / Cu3SnS4 composite photocatalyst, which has the following significant advantages:
[0027] (1) Synergistically improve the efficiency of photogenerated carrier separation
[0028] By constructing a heterojunction structure of Cl-doped Cu2O and Cu3SnS4 (see the attached manual) Figure 1 XRD diffraction peak double verification), combined with Cl- doping to regulate the Cu2O band structure (attached to the manual Figure 3 The absorption edge showed a red shift to 600 nm), which significantly optimized the interfacial charge transfer path.
[0029] Fluorescence spectrum (attached to the instruction manual) Figure 4 ) proved that the PL signal intensity of the composite catalyst COCS-2 was significantly quenched compared with that of the single component (Cl-Cu2O or Cu3SnS4), indicating that the recombination of photogenerated electron-hole pairs was effectively suppressed.
[0030] Transient fluorescence test (attached to the instruction manual) Figure 4 ) further verified that a new charge transfer channel was formed at the heterojunction interface, which improved the electron migration efficiency and directly promoted the enhancement of photocatalytic activity.
[0031] (2) Breakthrough solution to the photocorrosion problem of Cu2O
[0032] Cl- doping forms a stable structure in the Cu2O lattice (the Cl-Cu2O characteristic peak in XRD is consistent with JCPDS 05-0667). At the same time, the rapid charge separation at the heterojunction interface reduces the accumulation of holes on the Cu2O surface:
[0033] Cyclic stability test (attached to the instruction manual) Figure 2c) After COCS-2 was continuously subjected to five CO2 reduction cycles within 25 h, the CO yield only decreased by 11% (from 26.61 to 23.68 μmol·g -1 h-1), which is much better than undoped Cu2O-based materials (usually attenuated by >30%).
[0034] The improved stability is directly attributed to the inhibition of Cu2O oxidation by Cl doping and the directional carrier transfer mechanism of the heterojunction.
[0035] (3) Highly active and selective catalytic CO2 reduction
[0036] By adjusting the Cu3SnS4 loading (Examples 1-3), the following precise optimization of product selectivity was achieved:
[0037] a. Product yield breakthrough: COCS-2 (Cu3SnS4 loading 100 mg) simultaneously achieved CO (26.61), CH4 (33.68), C2H4 (15.99 μmol·g -1 The three products of h-1) are highly active, with the C2H4 yield being more than 16 times that of a single component.
[0038] b, unique selective regulation (attached to the instruction manual) Figure 2 d) The selectivity of COCS-2 for the high-value-added product C2H4 exceeds 30% (single Cl-Cu2O or Cu3SnS4 hardly produces C2H4), which is attributed to the heterojunction interface promoting the coupling reaction of *CO intermediates.
[0039] c. Loading optimization mechanism: Excessive Cu3SnS4 in COCS (such as COCS-3) will shield light absorption (see the instructions). Figure 3 a) The absorption intensity decreased, confirming that 100 mg was the optimal loading amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 These are the X-ray diffraction patterns of Cu2O, Cu3SnS4 obtained in the present invention and the Cu2O / Cu3SnS4 composite photocatalysts obtained in Examples 1-3, respectively.
[0041] Figure 2 This is a graph showing the yield of photocatalytic carbon dioxide reduction using the Cu2O and Cu3SnS4 composite photocatalysts obtained in the present invention and the COCS-1, COCS-2, and COCS-3 composite photocatalysts obtained in Examples 1-3, respectively.
[0042] Figure 3 It is the solid ultraviolet image of Cu2O, Cu3SnS4 obtained in the present invention and COCS-1, COCS-2, COCS-3 composite photocatalysts obtained in Examples 1-3 respectively;
[0043] Figure 4 These are the fluorescence and transient fluorescence images of the Cu2O, Cu3SnS4 and COCS-2 composite photocatalysts obtained in the present invention. DETAILED DESCRIPTION
[0044] The present invention will be described in detail below with reference to the following examples. However, it should be understood that the following examples are merely illustrative of the embodiments of the present invention and are not intended to limit the scope of the present invention.
[0045] The Cu2O, Cl-doped Cu2O, and Cu3SnS4 used in the present invention are prepared by the following methods:
[0046] Preparation of Cl-doped Cu2O by liquid phase reduction method:
[0047] First, 0.01 mol of copper acetate monohydrate (C4H6CuO4·H2O) was dissolved in 50 mL of deionized water and stirred until the solution was clear. Then, 35 mL of 1 M sodium hydroxide aqueous solution was added dropwise to the reaction system and stirred for 10 min. With the dropwise addition of sodium hydroxide aqueous solution, a blue flocculent precipitate gradually formed in the reaction system. After the reaction was completed, 17.5 mL of 2 M hydroxylamine hydrochloride (NH4OH·HCl) was added to the reaction system as a reducing agent. The reaction was stirred until the color of the reaction system gradually changed from dark blue to orange. The obtained orange solid product was centrifuged and washed multiple times with ethanol and deionized water. Finally, it was dried in a vacuum oven at 60°C for 12 h to obtain Cl-doped Cu2O.
[0048] Preparation of cuprous oxide (Cu2O) by precipitation method:
[0049] 10 g of sodium dodecyl sulfate (SDS) and 0.512 g of copper chloride dihydrate were dissolved in 400 mL of deionized water. 30 mL of a 1 M sodium hydroxide aqueous solution was then added and stirred for 15 min. 60 mL of a 0.2 M hydroxylamine hydrochloride aqueous solution was then added dropwise to the reaction system. The mixture was stirred for 30 min. Finally, the solid precipitate was collected and washed three times with deionized water and then with alcohol, and dried in a vacuum oven at 60°C for 12 h to obtain Cu2O.
[0050] Preparation of Cu3SnS4 by solvothermal method:
[0051] Take 0.05g Cu2O and dissolve it in 40mL deionized water, then add 175mg of tin tetrachloride pentahydrate (SnCl4·5H2O) and 300mg of L-cysteine, stir until the solution is homogeneous, then transfer the mixed solution to a polytetrafluoroethylene-lined autoclave and hydrothermally heat it at 140℃ for 12h. Finally, the reaction product is washed with water and alcohol three times each, and dried in vacuum at 60℃ for 12h to obtain Cu3SnS4.
[0052] Example 1
[0053] 0.01 mol (2 g) of copper acetate monohydrate (C4H6CuO4·H2O) was dissolved in 100 mL of deionized water and stirred evenly. 80 mg of Cu3SnS4 was added to the reaction system and stirred evenly. Then, 35 mL of a 1 M sodium hydroxide aqueous solution was added to the reaction system and stirred until a blue flocculent precipitate was formed in the reaction system. After the reaction was completed, 17.5 mL of a 2 M hydroxylamine hydrochloride aqueous solution was added to the reaction system as a reducing agent. After the stirring reaction was completed, the obtained solid precipitate was centrifuged and washed three times with ethanol and deionized water respectively. Finally, it was vacuum dried at 60°C for 12 h to obtain a Cl-doped Cu2O / Cu3SnS4 composite photocatalyst labeled COCS-1.
[0054] Example 2 is the same as Example 1, except that the amount of Cu3SnS4 added in Example 2 is 100 mg. The obtained Cl-doped Cu2O / Cu3SnS4 composite photocatalyst is labeled COCS-2.
[0055] Example 3 is the same as Example 1, except that the amount of Cu3SnS4 added in Example 3 is 120 mg. The obtained Cl-doped Cu2O / Cu3SnS4 composite photocatalyst is labeled COCS-3.
[0056] Comparative Example 1 is the same as Example 1, except that 17.5 mL of 2 M hydroxylamine hydrochloride aqueous solution in Example 1 is replaced with 17.5 mL of 1 M ascorbic acid aqueous solution. The photocatalyst obtained in Comparative Example 1 is designated as a Cu2O / Cu3SnS4 composite photocatalyst.
[0057] Determination of photocatalyst components:
[0058] In the field of photocatalysis, the crystal structures of Cl-doped Cu2O, Cu3SnS4, COCS-1, COCS-2 and COCS-3 were determined using X-ray diffraction technology. Figure 1 As shown, at 29.55 ° , 36.41 ° , 42.29 °, 52.45 ° and 61.34 ° The significant characteristic peaks of Cl-doped Cu2O can be identified at the top and bottom, corresponding to the (110), (111), (200, (211) and (220) crystal planes of Cl-doped Cu2O, respectively. This indicates that the synthesized Cl-doped Cu2O exhibits good crystallinity and high purity, which is consistent with the standard card (JCPDS05-0667).
[0059] At the same time, Cu3SnS4 is at 28.49 ° , 33.15 ° , 47.46 ° and 56.02 ° Diffraction peaks were observed at 100 nm and 100 nm, respectively, which were attributed to the (112), (020), (220) and (132) crystal planes of Cu3SnS4, which is consistent with the standard card (JCPDS 33-0501). Similarly, the diffraction peaks of Cl-Cu2O and Cu3SnS4 can be observed simultaneously in the COCS composites (COCS-1, COCS-2 and COCS-3), indicating that Cu3SnS4 was successfully loaded onto Cl-Cu2O. In addition, with the gradual increase of the Cu3SnS4 loading amount, the diffraction peak intensity of Cl-Cu2O observed in the COCS composite material was significantly weakened.
[0060] Performance Testing
[0061] Under simulated sunlight, deionized water was used as the reaction solution, and Cl-doped Cu2O, Cu3SnS4, COCS-1, COCS-2, COCS-3, and Cu2O / Cu3SnS4 were used as photocatalysts for CO2 reduction. The photocatalytic CO2 reduction reaction was carried out in a 260 mL sealed glass reactor at atmospheric pressure and ambient temperature. The specific reaction process parameters are as follows:
[0062] (1) Select a glass slide of appropriate size, wash it three times with deionized water and ethanol, place it in a Petri dish and dry it in an 80°C oven. Weigh 5 mg of sample with weighing paper, place it in a centrifuge tube, add 0.5 mL of deionized water, and sonicate for 1 min. Use a dropper to draw the liquid from the tube onto the Petri dish in the oven. After drying, the sample preparation is complete.
[0063] (2) Use a reactor as a reaction device, clean the residual liquid in the reactor with water, take 10 mL of water and add it to the reactor, put in a stirrer and a beaker, and place the beaker at an angle to ensure that there are no bubbles at the bottom of the cup. Use tweezers to clamp the glass piece in step 1 and place it flat on the beaker, then cover it with a lid. The black circle clearly indicates that the lid has been compacted. Lightly clamp the four clamps in opposite directions. After the four clamps are securely installed, tighten them again. The preparation of the reactor is complete;
[0064] (3) Introduce CO2 into the reactor and ventilate for 15 minutes. When the ventilation is completed, the valves on both sides of the reactor should be closed at the same time to prevent the entry of air. The ventilation is completed;
[0065] (4) Illumination: Use a 300W xenon lamp, turn on the stirring table, and adjust the distance between the lamp and the reactor to 5 cm;
[0066] (5) Activity test: After every 1 hour of illumination, the gas in the reactor was extracted and tested by gas chromatography. The total illumination time was 5 hours. The test results were analyzed as follows:
[0067] As the instruction manual Figure 2 As shown in a, when Cu3SnS4 is used as the photocatalyst, the yields of CO and CH4 are 2.08 μmol·g -1 ·h -1 and 1.1 μmol·g -1 ·h -1 When Cl-Cu2O was used as the photocatalyst, the yields of CO and CH4 were 1.94 μmol·g -1 ·h -1 and 0.5 μmol·g -1 ·h -1 Surprisingly, after Cl-Cu2O and Cu3SnS4 formed a heterostructure, the yields of CO and CH4 were greatly improved, and C2H4 with higher added value was also generated.
[0068] When COCS-2 was used as the photocatalyst, the maximum yields of CO, CH4, and C2H4 were 26.61, 33.68, and 15.99 μmol·g, respectively. -1 ·h -1 .
[0069] In addition, by adjusting the loading amount of Cu3SnS4 in the COCS photocatalyst, the selectivity and catalytic activity of the COCS photocatalyst for CO, CH4 and C2H4 can also be adjusted.
[0070] Compared with COCS-1 and COCS-3, the amount of Cu3SnS4 used in the preparation process of COCS-2 is more appropriate and its photocatalytic activity is better. The reason may be that excessive Cu3SnS4 loading will form a shielding effect, hindering the light absorption of Cl-Cu2O, thereby affecting the electron transfer between Cl-Cu2O and Cu3SnS4.
[0071] Instructions attached Figure 2 b shows a comparative test under normal light, argon, darkness, and no catalyst. The test results show that light, photocatalyst, and CO2 are necessary conditions for the CO2 reduction reaction to occur. Argon, darkness, and no catalyst are all single control experiments under normal light.
[0072] The stability of the photocatalyst after 5 cycles of CO2 reduction reaction within 25 hours was evaluated through the cyclic performance test of carbon dioxide photoreduction reaction. The test results are shown in the attached manual. Figure 2 c. COCS-2 has good photocatalytic stability, and the CO yield is only reduced by about 11%. Figure 2 d shows the selectivity of Cl-Cu2O, Cu3SnS4 and COCS composite photocatalysts to products, among which only COCS-2 can achieve a selectivity of more than 30% for C2H4.
[0073] Among them, the selectivity of Cu2O / Cu3SnS4 to CO is 14.11%, the selectivity to CH4 is 57.67%, and the selectivity to C2H4 is 28.22%.
[0074] The cycle performance test process is as follows:
[0075] The catalysts were placed in the same reactor (volume of 260 mL) respectively, and 10 mL of deionized water was added to the reactor. Carbon dioxide was introduced for 15 minutes. A 300W xenon lamp was used to simulate sunlight. The irradiation distance was 5 cm. The activity was tested every 1 hour of illumination. 5 hours was a group, and there were 5 cycles in total. After every 5 hours, carbon dioxide was introduced again and the catalysts were illuminated. This cycle was repeated 5 times, which was the cyclic performance test.
[0076] UV absorption performance:
[0077] The solid UV images of Cl-Cu2O, Cu3SnS4, COCS-1, COCS-2 and COCS-3 photocatalysts are shown in the attached manual. Figure 3 The UV-visible diffuse reflectance spectrum (UV-vis DRS) of COCS-2 is shown in the attached manual. Figure 3 As shown in a. Cl-Cu2O shows a steep absorption edge at 600nm, indicating that it has good absorption capacity in the visible light region. After introducing Cu3SnS4 on the basis of Cl-Cu2O, Cl-Cu2O / Cu3SnS4 shows a normal absorption edge. Compared with Cl-Cu2O, the absorption edge of COCS-2 has a red shift. In order to determine the band gap, based on the attached manual Figure 3 The Tauc curve shown in b shows that the optical band gap (Eg) of Cu3SnS4 is 1.65eV, and the optical band gap (Eg) of Cl-Cu2O is 2.09eV, which are direct semiconductors.
[0078] Charge separation efficiency test:
[0079] The fluorescence images of Cl-Cu2O, Cu3SnS4, COCS-1, COCS-2 and COCS-3 composite photocatalysts are shown in the attached manual. Figure 4 shown.
[0080] Generally speaking, the recombination rate of photogenerated carriers in a sample under light excitation is positively correlated with the intensity of the PL peak. In other words, the higher the PL peak intensity, the faster the recombination rate of photogenerated carriers, and vice versa. Figure 4 As shown in the figure, the fluorescence spectra of Cl-Cu2O, Cu3SnS4, COCS-1, COCS-2 and COCS-3 composites are displayed. The test results show that Cl-Cu2O and Cu3SnS4 display strong PL signals, which are caused by the rapid recombination of photogenerated carriers. Compared with Cu3SnS4, the PL intensity of COCS-2 shows more obvious quenching, indicating that the recombination of photogenerated charges and holes is effectively suppressed and the charge transfer efficiency is higher. This result is consistent with the photocatalytic activity. In addition, the electron transfer efficiency is significantly improved from Cl-Cu2O, Cu3SnS4 to COCS-2, which can be attributed to the new interface effect and the formation of heterostructures.
[0081] With the above-described preferred embodiments of the present invention as a guide, and with reference to the above description, relevant personnel are fully capable of making various changes and modifications without departing from the technical scope of this invention. The technical scope of this invention is not limited to the contents of the specification and must be determined according to the scope of the claims.
Claims
1. A Cl-doped Cu2O / Cu3SnS4 composite photocatalyst, characterized in that: The preparation method comprises the following steps: (1) Cu2O, tin salt and sulfur source are dissolved in deionized water, and Cu3SnS4 is prepared by a hydrothermal method under high temperature, high pressure and closed reaction conditions; (2) Add the Cu3SnS4 obtained in step (1) to the copper acetate aqueous solution, stir and disperse evenly, then add an alkaline solution to the reaction system, continue stirring to form a blue flocculent precipitate in the reaction system, and after the reaction is completed, add a reducing agent to the reaction system to reduce the Cu3SnS4 in the reaction system. 2+ All reduced to Cu + , and then the solid product is collected by solid-liquid separation. After the surface of the solid product is cleaned and dried, a Cl-doped Cu2O / Cu3SnS4 composite photocatalyst is obtained.
2. The Cl-doped Cu2O / Cu3SnS4 composite photocatalyst according to claim 1, characterized in that: The tin salt is tin tetrachloride hydrate.
3. The Cl-doped Cu2O / Cu3SnS4 composite photocatalyst according to claim 1, characterized in that: The sulfur source is cysteine.
4. The Cl-doped Cu2O / Cu3SnS4 composite photocatalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 140° C., and the reaction time is at least 12 h.
5. The Cl-doped Cu2O / Cu3SnS4 composite photocatalyst according to claim 1, characterized in that: The preparation method of Cu2O comprises the following steps: Surfactant and Cu 2+ The source is added to deionized water and stirred to disperse evenly. A precipitant is then added to the reaction system. After stirring to react to generate a blue flocculent precipitate, a hydroxylamine hydrochloride aqueous solution is added. The stirring reaction is continued until an orange solid precipitate is generated in the reaction system. The obtained precipitate is surface washed and dried to obtain cuprous oxide.
6. The Cl-doped Cu2O / Cu3SnS4 composite photocatalyst according to claim 5, characterized in that: The Cu 2+ The source is copper chloride hydrate.
7. The Cl-doped Cu2O / Cu3SnS4 composite photocatalyst according to claim 5, characterized in that: The surfactant is SDS.
8. The Cl-doped Cu2O / Cu3SnS4 composite photocatalyst according to claim 5, characterized in that: The precipitant is an alkaline solution.
9. The Cl-doped Cu2O / Cu3SnS4 composite photocatalyst according to claim 1, characterized in that: In step (2), the feed ratio of copper acetate to Cu3SnS4 is 0.01 mol:100 mg.
10. A method for photocatalytic CO2 reduction, characterized in that: The Cl-doped Cu2O / Cu3SnS4 composite photocatalyst according to any one of claims 1 to 9 is used as a photocatalyst for CO2 reduction.